The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10753-018-0850-3
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Protected from Kidney Ischemia Reperfusion Injury in Mice: Possible Mechanism Through Increasing Adenosine Generation via HIF-1α

Abstract: Ferulic acid (FA), derived from fruits and vegetables, is well-known as a potent antioxidant of scavenging free radicals. However, the role and underlying mechanism of FA on kidney ischemia reperfusion (I/R) injury are limited. Here, we explored the effects of FA on kidney I/R injury. The kidney I/R injury models were carried out by clamping bilateral pedicles for 35 min followed by reperfusion for 24 h. Mice were orally pretreated with different doses of FA for three times 24 h before I/R. The renal function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Anti-inflammatory HUVEC cells, mice, rats FA decreased the expression of caspase-1 [52], ICAM-1 [52], VCAM-1 [52], IL-18 [52], IL-1β [50,[52][53][54], IL-6 [50,54], TNF-α [53], and inhibited the phosphorylation of p38 and IκB [52].…”
Section: Antioxidantmentioning
confidence: 95%
See 1 more Smart Citation
“…Anti-inflammatory HUVEC cells, mice, rats FA decreased the expression of caspase-1 [52], ICAM-1 [52], VCAM-1 [52], IL-18 [52], IL-1β [50,[52][53][54], IL-6 [50,54], TNF-α [53], and inhibited the phosphorylation of p38 and IκB [52].…”
Section: Antioxidantmentioning
confidence: 95%
“…Additionally, VA can inhibit the production of pro-inflammatory cytokines such as TNF-α, IL-6, IL-1β, and IL-33 by down-regulating caspase-1 and NF-κB pathways [45][46][47] in mice or mouse peritoneal macrophages and mast cells. FA has also been reported to attenuate both oxidative stress and inflammation potentially by suppressing the production of free radicals (ROS and NO in rats, rat intestinal mucosal IEC-6 cell, or murine macrophages) [48][49][50], enhancing Nrf2 expression and down-stream antioxidant enzymes (SOD and CAT in rats or swiss albino mice) [48,51], and inhibiting the activation of proinflammatory proteins (p38 and IκB in HUVEC cells) [52] and cytokines production, such as IL-18 in HUVEC cells [52], IL-1β in mice [53], IL-6 in obese rats [54], and TNF-α in mice [53]. However, both VA and FA showed a limited effect on the activation of MAPK pathway and production of inflammatory cytokines, such as monocyte chemoattractant protein-1 (MCP-1) and TNF-α in a high-fat diet-induced mouse model of nonalcoholic fatty liver disease [41].…”
Section: Biological Functions Of C3g-msmentioning
confidence: 99%
“…Ferulic acid (FA), phenol compound present in the wall of plants, is a major active ingredient in some traditional Chinese medicine(TCM), such as ferula asafetida, angelica, ligusticumwallichii, which are always used to improve microcirculation of ischemic diseases in TCM prescription [9,10]. Nowadays, a growing body of research findings demonstrated that FA suppressed detrimental immunoreactions under various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic acid (FA), phenol compound present in the wall of plants, is a major active ingredient in some traditional Chinese medicine(TCM), such as ferula asafetida, angelica, ligusticumwallichii, which always used to improve microcirculation of ischemic diseases in TCM prescription [8,9]. Nowadays, a growing body of research demonstrated that FA suppressed detrimental immunoreactions under various conditions.…”
Section: Introductionmentioning
confidence: 99%